Evaluating the performance of external auditor during COVID-19: The case of dysfunctional audit behaviour in Indonesia - Lili Sugeng Wiyantoro; Chen Yan; Liu Yuanyuan (Cogent Business & Management, 2023)
We investigate the factors impacting dysfunctional audit behaviour (DAB) in audit companies in Indonesia during COVID-19. We additionally examine at how organisational commitment (OC), employee performance (EP), and turnover intention (TI) play a role as mediators in the relationship between locus of control (LOC) and DAB, how OC and TI play a role as mediators between EP and DAB, and how OC plays a role as a mediator between TI, auditor position (AP), and DAB. This study made use of the structural equation model (SEM) and the SmartPLS methodology. The processed data includes 118 external auditor replies received between May and October 2022. DAB was positively impacted by LOC, TI, time budget pressure (TBP), and AP, according to our findings. DAB is negatively affected by EP and OC. The relationship between LOC and DAB is mediated via OC and EP. EP and DAB interactions are mediated via OC and TI. The relationship between TI, AP, and DAB is mediated by OC. Indonesia's first comprehensive causal model examined COVID-19 DAB hazards. DAB assessed COVID-19 auditors. This study addresses audit firm and external auditors. Auditing, reviews, auditor monitoring, and peer-reviewing audit organisations prevent DAB. DAB can lower audit quality and fail audits.
Keywords: H83; L21; L44; M42; 650; auditor position; dysfunctional audit behaviour; employee performance; locus of control; organisational commitment; time budget pressure; turnover intention